TWO-DIMENSION FINITE ELEMENT METHOD GEOMETRY MODELING OF POLYCRYSTALLINE MATERIAL MICRO-STRUCTURE - CHEN Zhen; ZHOU JinYu; ZHU FuXian (Jixie qiangdu)
Finite element modeling of polycrystalline micro-structure is one of the important contents of polycrystalline metal material research.In view of the problem of the limited application of traditional methods and the difficulty of precisely modeling for Polycrystalline,Polycrystalline modeling method was proposed in this paper.This method generated weight circles according to the specified grain size distribution first.Normal circles generation method and generating new circle based on the interference types were analyzed and then divided weight circles boundaries.At last,combining with ANSYS,modeling and mesh experiments were carried out according to four specified functions.This method can model according to all kinds of grain size distributions within a small error range,which is helpful to improve the accuracy and reliability of the simulation and its operation is simple.